2018
DOI: 10.3390/genes9100496
|View full text |Cite
|
Sign up to set email alerts
|

An Analytic Approach Using Candidate Gene Selection and Logic Forest to Identify Gene by Environment Interactions (G × E) for Systemic Lupus Erythematosus in African Americans

Abstract: Development and progression of many human diseases, such as systemic lupus erythematosus (SLE), are hypothesized to result from interactions between genetic and environmental factors. Current approaches to identify and evaluate interactions are limited, most often focusing on main effects and two-way interactions. While higher order interactions associated with disease are documented, they are difficult to detect since expanding the search space to all possible interactions of p predictors means evaluating 2p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…A case‐control study of 152 Japanese patients with SLE and corresponding controls reported an additive interaction between tumor necrosis factor receptor superfamily, member 1B ( TNFRSF1B ) and smoking [59]. Potential G–E interactions between smoking and/or second‐hand smoke have focused on SNPs located on additional SLE susceptibility genes, including those related to interleukin‐10 ( IL‐10 , which may be linked to SLE risk in currently smoking individuals) [60], interleukin‐33 ( IL‐33 ; also linked to SLE risk in current smokers) [61], integrin subunit alpha M ( ITGAM ; linked to SLE risk in the setting of childhood second‐hand smoke) [62], and estrogen receptor 1 ( ESR1 , linked to SLE risk in current smokers) [63].…”
Section: Chemical and Physical Exposuresmentioning
confidence: 99%
“…A case‐control study of 152 Japanese patients with SLE and corresponding controls reported an additive interaction between tumor necrosis factor receptor superfamily, member 1B ( TNFRSF1B ) and smoking [59]. Potential G–E interactions between smoking and/or second‐hand smoke have focused on SNPs located on additional SLE susceptibility genes, including those related to interleukin‐10 ( IL‐10 , which may be linked to SLE risk in currently smoking individuals) [60], interleukin‐33 ( IL‐33 ; also linked to SLE risk in current smokers) [61], integrin subunit alpha M ( ITGAM ; linked to SLE risk in the setting of childhood second‐hand smoke) [62], and estrogen receptor 1 ( ESR1 , linked to SLE risk in current smokers) [63].…”
Section: Chemical and Physical Exposuresmentioning
confidence: 99%
“…Unlike statistical models that require that data meet certain strong underlying assumptions, machine learning probes data to identify an underlying structure using an iterative approach to learn from the data. A specific machine learning technique, called Logic Forest, iteratively investigates the main data effects and the sample space of all interactions without any specific a priori assumptions . As such, this method represents an optimal approach to identify potentially associated predictors and combinations of associated predictors without any user input bias.…”
Section: Introductionmentioning
confidence: 99%
“…This special issue presented new methodologies in the context of gene-environment, tissue-specific gene expression and how external factors or host genetics impact the microbiome [8][9][10]. Wolf and colleagues developed an analytical approach for identifying the main effects and interactions between genetic and environmental factors linked to a disease outcome [8].…”
mentioning
confidence: 99%
“…This special issue presented new methodologies in the context of gene-environment, tissue-specific gene expression and how external factors or host genetics impact the microbiome [8][9][10]. Wolf and colleagues developed an analytical approach for identifying the main effects and interactions between genetic and environmental factors linked to a disease outcome [8]. The method involves selection of candidate genetic and/or environmental factors, utilization of a machine learning algorithm Logic Forest to identify the salient effects and interactions in the disease, followed by confirmation of the association between interactions identified by the algorithm using logistic regression.…”
mentioning
confidence: 99%
See 1 more Smart Citation